2019
DOI: 10.12968/bjmh.2019.8.3.145
|View full text |Cite
|
Sign up to set email alerts
|

Exploring how awareness of character strengths can benefit mental health nurses

Abstract: This is the third in a series of articles that explores the meaning of positive psychology and the importance of applying the latest research findings for the wellbeing of the mental health workforce. It will focus on character strengths as a positive psychology intervention from its development to present day use and how it is relevant to mental health nursing. The activities provided in the boxes throughout the article will help the reader identify their own strengths and understand how to further develop th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…In a 6-year longitudinal study, it was found that the students with higher levels of hope showed better overall grade averages even after controlling for entrance exam scores (Snyder et al, 2002 ). The university is the ideal place to cultivate the strengths that will result in better professional performance, while increasing the vocation for the profession (Harzer & Ruch, 2015 ; Macfarlane, 2019 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a 6-year longitudinal study, it was found that the students with higher levels of hope showed better overall grade averages even after controlling for entrance exam scores (Snyder et al, 2002 ). The university is the ideal place to cultivate the strengths that will result in better professional performance, while increasing the vocation for the profession (Harzer & Ruch, 2015 ; Macfarlane, 2019 ).…”
mentioning
confidence: 99%
“…Based on these antecedents, scientific interest in the study of character strengths in students who pursue college programmes involving high levels of stress and high dropout rates (such as nursing courses) has increased (Burke et al, 2009;Grady & Cantor, 2012;Harzer & Ruch, 2015;Littman-Ovadia & Steger, 2010;Macfarlane, 2019;Xie et al, 2020). In this sense, strengths such as self-regulation and prudence have been shown to favour adaptation to university (Shin et al, 2015), and enthusiasm, hope, curiosity, love, and gratitude are most strongly related to overall job satisfaction (Heintz & Ruch, 2020;Macfarlane, 2019). In a 6-year longitudinal study, it was found that the students with higher levels of hope showed better overall grade averages even after controlling for entrance exam scores (Snyder et al, 2002).…”
mentioning
confidence: 99%
“…The five character strengths that people emphasize the most in terms of their identity are known as signature strengths. Signature strengths can naturally affect daily behavior (Macfarlane, 2019). It is possible that the five character strengths, which are the most in LSCC that aims to change behavior through teaching, will affect the signature strengths of the students.…”
Section: Resultsmentioning
confidence: 99%
“…There are two non-research papers (Macfarlane, 2019;Powell et al, 2015) and five research papers (Delgado et al, 2020;Foster, Cuzzillo, & Furness, 2018;Foster, Shochet, et al, 2018;Gillet et al, , 2020). Of the seven papers, one was an expert opinion (Macfarlane, 2019), one was a critical evaluation of literature (Powell et al, 2015), five were nonexperimental studies including a qualitative inquiry, a prospective study (Foster, Shochet, et al, 2018), a crosssection survey (Konttila et al, 2020), and the results of a national survey (Delgado et al, 2020) and one was a quasi-experimental (Foster, Cuzzillo, & Furness, 2018).…”
Section: Summary Of Articlesmentioning
confidence: 99%